Influence of tool geometry and process parameters on torque, temperature, and quality of friction stir welds in dissimilar al alloys - Manuel, Neves (2021)
In the current investigation, the influence of the tool geometry, the position of the materials in the joint, the welding speed on the temperature and torque developed, and on the quality of the welds in dissimilar and tri-dissimilar T joints were analysed. The aluminium alloys used were AA2017-T4, AA6082-T6, and AA5083-H111 and the friction stir welds were performed with identical shoulder tools, but with either a pin with simple geometry or a pin with progressive geometry. Progressive pin tools proved to be a viable alternative in the production of dissimilar and tri-dissimilar welds, as they provide a larger tool/material friction area and a larger volume of dragged material, which promotes an increase in the heat generated and a good mixing of the materials in the stir zone, although they require a higher torque. Placing a stronger material on the advancing side also results in a higher temperature in the stir zone but requires higher torque too. The combination of these factors showed that tools with a progressive pin provide sound dissimilar and tri-dissimilar welds, unlike single-pin tools. The increase in the welding speed causes the formation of defects in the stir zone, even in tri-dissimilar welds carried out with a tool with a progressive pin, which impairs the fatigue strength of the welds.